Arbitrariness, Iconicity, and Systematicity in Language. Issue 10 (October 2015) - Dingemanse, Mark; Blasi, Damián E.; Lupyan, Gary; Christiansen, Morten H.; Monaghan, Padraic
Abstract : The notion that the form of a word bears an arbitrary relation to its meaning accounts only partly for the attested relations between form and meaning in the languages of the world. Recent research suggests a more textured view of vocabulary structure, in which arbitrariness is complemented by iconicity (aspects of form resemble aspects of meaning) and systematicity (statistical regularities in forms predict function). Experimental evidence suggests these form-to-meaning correspondences serve different functions in language processing, development, and communication: systematicity facilitates category learning by means of phonological cues, iconicity facilitates word learning and communication by means of perceptuomotor analogies, and arbitrariness facilitates meaning individuation through distinctive forms. Processes of cultural evolution help to explain how these competing motivations shape vocabulary structure. Trends: The principle of arbitrariness accounts only partly for attested form-to-meaning correspondences in the vocabularies of the languages of the world. Recent research has uncovered substantial patterns of non-arbitrariness in language. Two common forms of non-arbitrariness are iconicity and systematicity, each with complementary advantages in learning and communication. A fully arbitrary vocabulary is unlikely to be a stable feature of natural languages, because form-to-meaning correspondences are shaped by cultural evolutionary processes which favour not just discriminability but also learnability and communicative utility.